ANTI HEPATITIS C ACTIVITY AND TOXICITY OF Scoparia dulcis LINN. HERB - Widyawaruyanti, Aty; Permanasari, Adita Ayu; Hidayatus, Laila Nur; Tumewu, Lidya; Wahyuni, Tutik Sri; Hafid, Achmad Fuad (Indonesian Journal of Tropical and Infectious Disease, 2020)
Hepatitis C Virus (HCV) infection is a serious public health problem since HCV is the ribonucleic acid (RNA) virus that  easy to mutate. The HCV standard treatment  has rapidly developed but the possibility of resistance and effectiveness of treatment needs to be considered. The medicinal plants are a source of various compounds that may potentially cure diseases including infectious diseases. Since a long years ago, medicinal plants were famous as an inherited treatment that believed to cure the disease. One of the medicinal plants is Scoparia dulcis (S. dulcis) that belongs to Scrophulariaceae family and traditionally used as remedies for digestive problems, hypertension, diabetes mellitus, bronchitis, and as an analgesic & antipyretic agent. The previous report showed that S. dulcis was known active as an antiviral against Herpes Simplex Virus (HSV) type 1 in vitro and in vivo. The aim of the study is to determine the biactivity potential of S. dulcis against HCV. Scoparia dulcis was extracted using 80% ethanol (EE) then further separated by liquid-liquid fractionation using dichloromethane (DCMF), ethyl acetate (EAF), butanol solvent (BF) and water (WF). The in vitro anti-HCV analysis was performed with Huh7it cells and HCV JFH1 (genotype 2a) by determining inhibition concentration 50 (IC50). The toxicity (Cytotoxicity Concentration 50, CC50) test was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and mechanism of action were analyzed using time addition experiment.   Phytochemical groups as the suspected active compounds of S. dulcis were identified by Thin Layer Chromatography (TLC) and observed under UV 254 nm, UV 365 nm, before and after sprayed using H2SO4 10% and heated at 105oC for 5 minutes. The IC50 test result of 80% EE and DCMF showed anti-HCV activity with a value of 12.7±4.8 µg/ml and 5.8±0.69 µg/ml, while EAF, BF, and AF respectively resulted in IC50 value of  >100 µg/ml that suggested there was no inhibition effect on HCV JFH1.  The DCMF was the most active fraction but toxic to the cell with CC50 value >23 µg/ml and selectivity index (SI) >3.9. According to the time addition experiment data, DCMF of S. dulcis inhibited post entry step HCV JFH1 infection that it means the possibility was to inhibit virus replication and or virion release. Scoparia dulcis contain chlorophyll, flavonoids and terpenoids as the suspected active compounds for inhibition of HCV JFH1 infecton. Futher study of post-entry inhibitions of HCV infection was needed.